Participatory Communication as a Strategy for Empowering Indigenous Communities in Customary Land Rights Legislation - Tetti Nauli Panjaitan; Hilarius Bambang Winarko (Journal of Universal Community Empowerment Provision, 2026)
This study examines participatory communication practices in the legislative process concerning customary land rights (tanah ulayat) of the Batak Toba indigenous law community, particularly in the implementation of Regional Regulation of Toba Regency Number 1 of 2020. Customary land rights possess not only economic value but also cultural, historical, and collective identity dimensions. However, in legislative practice, indigenous communities often do not receive equal opportunities for participation. This research employs a qualitative approach with a case study method in four agrarian conflict areas: Sigapiton, Lumban Sitorus, West Lumbanrau, and Gurgur Aek Raja. Data were collected through in-depth interviews, participatory observation, and analysis of legal documents and media sources. Data analysis was conducted using the Miles and Huberman model as well as thematic analysis. The findings reveal that communication in the legislative process remains elitist and has not been fully dialogical. Structural barriers in the form of bureaucratic dominance and cultural barriers arising from differences in value systems weaken indigenous community participation. This study proposes a participatory communication model based on local wisdom that emphasizes deliberative dialogue, customary deliberation, and equality of participation. These findings contribute to the development of participatory communication theory within the context of legal pluralism and provide practical recommendations for the formulation of inclusive policies.